Cognitive effects of adjunctive N-acetyl cysteine in psychosis. Issue 5 (29th November 2016) - Rapado-Castro, M.; Dodd, S.; Bush, A. I.; Malhi, G. S.; Skvarc, D. R.; On, Z. X.; Berk, M.; Dean, O. M.
Abstract : Background: Cognitive deficits are predictors of functional outcome in patients with psychosis. While conventional antipsychotics are relatively effective on positive symptoms, their impact on negative and cognitive symptoms is limited. Recent studies have established a link between oxidative stress and neurocognitive deficits in psychosis. N -acetylcysteine (NAC), a glutathione precursor with glutamatergic properties, has shown efficacy on negative symptoms and functioning in patients with schizophrenia and bipolar disorder, respectively. However, there are few evidence-based approaches for managing cognitive impairment in psychosis. The present study aims to examine the cognitive effects of adjunctive NAC treatment in a pooled subgroup of participants with psychosis who completed neuropsychological assessment in two trials of both schizophrenia and bipolar disorder. Method: A sample of 58 participants were randomized in a double fashion to receive 2 g/day of NAC ( n = 27) or placebo ( n = 31) for 24 weeks. Attention, working memory and executive function domains were assessed. Differences between cognitive performance at baseline and end point were examined using Wilcoxon's test. The Mann–Whitney test was used to examine the differences between the NAC and placebo groups at the end point. Results: Participants treated with NAC had significantly higher working memory performance at week 24 compared with placebo ( U = 98.5, p = 0.027). Conclusions: NAC may have an impact on cognitive performance in psychosis, as a significant improvement in working memory was observed in the NAC-treated group compared with placebo; however, these preliminary data require replication. Glutamatergic compounds such as NAC may constitute a step towards the development of useful therapies for cognitive impairment in psychosis.